Pollen Morphology and Systematic Implications of the Tribes Ranunculeae and Anemoneae in Ranunculaceae - Junaid, Muhammad; Zafar, Muhammad; Ahmad, Mushtaq; Sohail, Amir; Shah, Hussain; Ahmad, Shabir; Jelani, Ghulam; Ali, Nisar; Ullah, Najeeb; Ullah, Ateef; Zamin, Sher (Phytotaxa, 2026)
The present study was conducted to investigate the systematic importance of Tribes Ranunculeae and Anemoneae in Ranunculaceae from Pakistan. Using light microscopy and scanning electron microscopy, this study presented the first detailed palynological analysis of the tribes. Quantitative and qualitative features of pollen grains were investigated for accurate identification of plant species. The results showed that pollen was endoaperturate, with studied apertures as tricolpate, tricolporate, tetracolpate, and trizonocolpate. The parasyncolpate type of aperture was present only in Ranunculus repens in the present study. The ornamentation of colpi varied from species to species within the same genus, while scabrate, gemmate, and verrucate colpus patterns with micro-spinule-like projections were the most predominant in the tribes. The highest pollen diameter was observed in Ranunculus arvensis (65.6 µm), while the lowest was in Clematis grata (23.8 µm). Microechinate, scabrate, fossulate, striate, and verrucate microperforated surface ornamentation types were recorded through scanning electron microscopy for accurate taxa identification. Our results suggest that palynological features are effective tools for resolving ambiguities among closely related species, such as Ranunculus, and for revealing taxonomic relationships at the tribal and genus levels.